PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS V SDN 13 SINGKAWANG : PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP KETERAMPILAN MENULIS NARASI SISWA KELAS V SDN 13 SINGKAWANG - Esti, Nindya; Oktavia, Wahyuni; Suwanto, Insan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Abstract: This research aims to 1) find out whether there are differences in narrative writing skills that use the picture and picture model and classes that use the conventional model in narrative writing activities in class V at SDN 13 Singkawang. 2) to find out how much influence the picture and picture learning model has on narrative writing skills in class V Indonesian language learning at SDN 13 Singkawang. The type of research used is quantitative with a nonequivalent control group design. The population in this study were all class V students at SDN 13 Singkawang. And the samples for this study were 23 students in the experimental class VA and 24 students in the control class VB. The results of the research show that 1) The t test shows t_count > t_(table), namely 3.2679 > 2.01410, so it can be concluded that there is a difference in the ability to write narratives between the class that uses the picture and picture learning model and the class that uses the conventional model in the narrative writing ability of class V students at SDN 13 Singkawang; 2) test the magnitude of the influence (effect size) of the picture and picture learning model on students' narrative writing skills, the results are influential with the effect size being in the high criteria with a value of 0.813 in the range E_Sd>0.8. The of this research indicate that there is a need for a picture and picture model in learning to improve students' narrative writing skills so that it can have a positive impact on Indonesian language learning skills. Keywords: Influence, model, picture and picture, narrative writing skills.